Open access from the point of view of the Polish author - Dziakowicz, Karolina (Wydawnictwo C.H. Beck, 2019)
The purpose of this article is to analyse the phenomenon of Open Access from the point of view of the author subject to the Polish legal regime. This text describes not only the genesis and general assumptions of the Open Access movement, but also indicates solutions that can be used by the author based on the provisions of Polish law. The open science thesis that assumes the acceptance of the principle of openness at all stages of work and scientific communication is more and more proclaimed. This revolution consists not only of technological changes, but above all in the consciousness of people from the world of science, which thanks to digital tools appeal again to the fundamental principles of an effective scientific process – openness and readiness to cooperate with others. A society that is more and more aware of its rights has begun to demand disclosure of research results achieved by public funds. Thus, the views that scientific knowledge is in fact a public property and its use (subject to the principle of including authors’ rights to published materials) should not be subject to restrictions that are increasingly and more clearly proclaimed. Open access can speed up research in any field and in any language. The most important, however, seems to be the realization of what it really is, why it turns out to be beneficial, how to implement it, and how it is best achieved.
Keywords: Open Access; copyright; publication; work; determination of the rightholder; computerization